Analisis Margin Pemasaran Udang Vaname (Litopenaeus vannamei) Di CV Jaya Tirta Vaname Probolinggo, Jawa Timur (Studi Kasus) - Andi Baso Adil Natsir; Sumarni; Elsa Handayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Vaname shrimp is a high-value commodity; however, long marketing channels can potentially disadvantage producers due to inefficient margins. This study aims to analyze the marketing channels, marketing margins, farmer’s share, and marketing efficiency of Vaname shrimp at CV Jaya Tirta Vaname. The research was conducted from June to December 2025 using a quantitative descriptive method. Data collection involved a combination of three techniques: face-to-face interviews, review of supporting documents, and a search of relevant literature. A saturated sampling method was used, comprising one producer, two collectors, and one retailer. The study identified two marketing channels utilized by CV Jaya Tirta Vaname. Marketing Channel I involves the chain: CV Jaya Tirta Vaname collector processing industry. This channel markets the total harvest of fresh, large-sized shrimp (sizes 40–59) at a higher selling price, resulting in a marketing margin of Rp11,000/kg and a farmer’s share of 86.03%. Marketing Channel II involves the chain: CV Jaya Tirta Vaname retailer local market end consumer. This channel markets shrimp that died during the siphoning process of cultivation; these are smaller (sizes 60–72) and sold at a lower price, yielding a marketing margin of Rp7,210/kg and a farmer’s share of 76.74%. Marketing efficiency was recorded at 6.98% for Channel I and 8.06% for Channel II. Based on applicable efficiency standards, both channel patterns fall below the 33% threshold, indicating that the entire marketing chain can be categorized as efficient.